CLINICAL AND INSTRUMENTAL ASSESSMENT OF MORPHO-FUNCTIONAL CONDITION OF THE HEART AND VASCULATURE IN COMORBIDITY OF ARTERIAL HYPERTENSION AND DIABETES MELLITUS TYPE 2 - N. Z. Babayeva (Евразийский Кардиологический Журнал)
The aim of this study was to investigate the heart and common carotid arteries (CCA) morphological and functional condition and the lipid spectrum in patients with arterial hypertension (AH) and type 2 diabetes mellitus (DM-2).Material and methods. The study included 144 patients with varying degrees of AH, 103 had AH without DM-2 (AH subgroup) and 41 patients with AH and DM-2 (AH+DM-2 subgroup). In all investigated patients the blood plasma lipid profile, echocardiographic examination of the heart and ultrasound Doppler examination of the CCA were carried out. The results. Significant differences between the AH and AH+DM-2 subgroups were discovered, which confirmed the significant effect of DM-2 on various parameters of the cardiovascular system. The lipid profile in the above mentioned subgroups has not significant differences, but some separated indices (TG, VLDL) in the AH+DM-2 subgroup were comparatively higher and HDL level lower comparing to AH subgroup. Marked changes in echocardiographic parameters, such as lowering of left ventricle (LV) ejection fraction (EF), significant increase of interventricular septum and LV posterior wall thickness, high frequency of LV hypertrophy detection, diastolic dysfunction, diffuse hypokinesis and dilatation of the heart cavities in the AH+DM-2 subgroup were confirmed. A significant rise of CCA intima-media thickness also was found in the AH+DM-2 in comparison with AH subgroup, which proved the essential role of comorbidity of AH and DM-2 in the heart and vessels remodeling. The conclusion. The results of the study confirm the role and significance of comorbidity of AH with DM-2 in the development of the cardiovascular system pathological changes.